2010
DOI: 10.1093/bja/aeq267
|View full text |Cite
|
Sign up to set email alerts
|

Altered cardiovascular responses to tracheal intubation in patients with complete spinal cord injury: relation to time course and affected level

Abstract: The cardiovascular and catecholamine responses to intubation change as a function of the time elapsed and the level of the cord injury. In this study, the pressor response to tracheal intubation was abolished in the quadriplegics but not in paraplegics; indeed, it was enhanced at 10 yr or more since injury in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…9 After high-level SCI the spinal sympathetic pathways involved in maintaining HR are disrupted, leaving the heart with unopposed parasympathetic vagal tone 40 . This imbalance creates vulnerability to exogenous stimuli such as tracheal suction, 26 but also to spontaneous episodes of bradycardia. 9 The incidence of bradycardia peaked at days 4-6 8,9,12 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 After high-level SCI the spinal sympathetic pathways involved in maintaining HR are disrupted, leaving the heart with unopposed parasympathetic vagal tone 40 . This imbalance creates vulnerability to exogenous stimuli such as tracheal suction, 26 but also to spontaneous episodes of bradycardia. 9 The incidence of bradycardia peaked at days 4-6 8,9,12 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the specific exposure category ( Table 3) the authors studied the response in HR to various stimuli including effects of exercise, penile vibro-stimulation, tracheal suction and intubation, facial water-immersion, and tilting in individuals with SCI. 8,15,16,[20][21][22][23][24][25][26] Claydon et al 15 reported that 6 of 13 male participants with cervical SCI developed new bradycardia when undergoing penile vibro-stimulation for sperm retrieval. Furthermore, some of these participants had episodes of atrial premature beats and VPB during or after the procedure.…”
Section: Specific Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, medications that further diminish the catecholamine surge may result in exacerbation of hypotension and bradycardia [25,26]. Tracheal or laryngeal manipulation can also stimulate a bradycardic response in these patients, as can any degree of hypoxia [27,28].…”
Section: Airwaymentioning
confidence: 99%